2015
DOI: 10.18186/jte.94189
|View full text |Cite
|
Sign up to set email alerts
|

Aerodynamic Performance of Small-Scale Horizontal Axis Wind Turbines Under Two Different Extreme Wind Conditions

Abstract: Aerodynamic performance of two small-scale horizontal axis wind turbines are analyzed under the extreme operating gust and extreme direction change conditions with initial wind speeds of 7, 10, 13, 15 and 20 m/s. Performance predictions are performed using computational fluid dynamics, and time variations of shaft torque and hub bending moment produced by the turbines are presented and compared with each other. Sectional flow field and sectional blade loading details along with surface skin friction line predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Further challenges are dictated by the ambition of employing micro-wind turbines in urban environments: in this context, the demand of mitigating noise and vibration is evidently more pressing, and, at the same time, the environment is complex and turbulent [8][9][10][11][12][13]. The strongly varying loads to which a micro-wind turbine can be subjected in an urban environment [14] can cause heavy stresses on all the components, with large noise [15][16][17][18] and vibrations and risks of damage and breakage of the device [19]. Further, the use of micro-wind turbines in urban environments, where the average wind intensity is commonly quite low and the turbulence structure might be complex, requires the optimization of the design of the blades [4] and of the performances near the start-up.…”
Section: Introductionmentioning
confidence: 99%
“…Further challenges are dictated by the ambition of employing micro-wind turbines in urban environments: in this context, the demand of mitigating noise and vibration is evidently more pressing, and, at the same time, the environment is complex and turbulent [8][9][10][11][12][13]. The strongly varying loads to which a micro-wind turbine can be subjected in an urban environment [14] can cause heavy stresses on all the components, with large noise [15][16][17][18] and vibrations and risks of damage and breakage of the device [19]. Further, the use of micro-wind turbines in urban environments, where the average wind intensity is commonly quite low and the turbulence structure might be complex, requires the optimization of the design of the blades [4] and of the performances near the start-up.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the IEC specification of wind direction component of the ECD case showed substantially overestimated value for all the mean wind velocities. In order to analyze the effect of extreme wind conditions on the aerodynamic performance of HAWTs, Alpman compared the wind turbine performance at the wind velocities of 7, 10, 13, 15, and 20 m/s, using CFD simulations (Emre Alpman, 2015). As can be seen from this research, variations in wind velocity had non-significant impact on the blade loads at low wind velocities.…”
Section: Introductionmentioning
confidence: 97%
“…In natural, wind is usually unsteady with high levels of turbulence in the short time, resulting in air flows characterized by rapid changes in the speed and direction (Burton et al, 2001;Emre Alpman, 2015;Li et al, 2016a). One of the wind conditions is called the extreme wind direction change, which is being focused on in this study.…”
Section: Introductionmentioning
confidence: 99%
“…The extreme wind events can lead to very large loads causing fatigue or damage to some turbine components. Wind is usually unsteady with high levels of turbulence in the short time, resulting in air flows characterized by rapid changes in the speed and direction (Burton et al, 2001;Alpman, 2015;Li et al, 2016a).…”
Section: Introductionmentioning
confidence: 99%